Experimental Assessment of Combustion, Performance and Emission Characteristics of a CI Engine Fueled with Biodiesel and Hybrid Fuel Derived from Waste Cooking Oil. Issue 4 (6th February 2019) - Singh, Deepak; Deep, Akash; Sandhu, S. S.; Sarma, A. K.
Abstract : Akin to biodiesel, hybrid fuels are gaining attention as a substitute to petro‐diesel, because of low processing cost of fuel production, having comparable engine performance, and significantly lower amount of emissions. This study presents experimental investigations on production of biodiesel and hybrid fuels from waste cooking oil and analyzes its behavior in an existing CI engine without the alteration of fuel injection settings. The biodiesel was produced by transesterification process and hybrid fuels were prepared by 3‐phase titration method. The physico‐chemical properties of fuels were evaluated as per ASTM/EN standards and compared with petro‐diesel. Biodiesel, blends of biodiesel and hybrid fuels were then analyzed for engine performance, emission, and combustion characteristics at constant speed and variable loading conditions. Biodiesel blend B30 showed higher brake thermal efficiency, lower brake specific energy consumption, and lower exhaust emissions (except NOx level), whereas, hybrid fuels showed a significant reduction in NOx level and comparable other exhaust emissions (except unburnt hydrocarbon) at the cost of lower brake thermal efficiency when compared with diesel. © 2019 American Institute of Chemical Engineers Environ Prog, 38:e13112, 2019